(untitled) (European Journal of Pure and Applied Mathematics, 2025)
Irregularity indices are topological indices by nature. They are highly helpful for determining the quantitative topography of nonregular graphs’ molecular structures. Both the quantitative structure-property relationship (QSPR) and the quantitative structure-activity relationship (QSAR) depend heavily on the computation of abnormalities in a graph. It is made up of several chemical and physical characteristics, including resistance, enthalpy, entropy, toxicity, melting and boiling points, and entropy. This paper examines the application of different irregularity indices to identify irregularity measurements (IMs) in the network of carbon nanocone molecules C N C_t(m), for t=4,5, and t. We have used different irregularity indices such as Irdif(ξ_t) , Al(ξ_t), Irl(ξ_t), Irlu(ξ_t), Irlf(ξ_t), Irf(ξ_t), Irla(ξ_t), Ird 1(ξ_t), Ira(ξ_t), Irga(ξ_t), Irb(ξ_t) & Irr _t(ξ_t). Comparative graphic measures of irregularity in C N C_4( m), C N C_5( m) and C N C_t( m) have also been examined and presented. We are interested in creating new formulas to gain a better understanding of irregularity measures in carbon nanocones using the indices described above.